Comparative histological study between MTA and Portland cement - Cristina de Jesus REISS-ARAÚJO; Kércya da Silva PAIM; Marcelo de Azevedo RIOS; Diana Santana de ALBUQUERQUE; Flares BARATTO FILHO; José Roberto VANNI (Revista Sul-Brasileira de Odontologia, 2009)
Introduction: Several studies have demonstrated the effectiveness of MTA as a promising material in Dentistry. There is a possibility that the Portland cement may provide the same results of MTA due to the similar composition of both materials. Objective: comparing the MTA and Portland cement by means of histological observation. Material and methods: Two groups of five wistar rats (Rattus novergicus) each were submitted to surgery at the filtrum area for insertion of a polyethylene tube containing MTA (left side) and Portland cement (right side). After flap closure, the animals were placed in isolation and two different periods (2 and 12 weeks) were selected to sacrifice the animals. Blocks were obtained from the animals, stored in 10% formalin solution and submitted to histological preparation. All blocks were observed under a light microscope. Results: The results showed that the MTA yielded a less intense histological reaction than the Portland cement in 2-week period. In the 12-week period, the histological results were very similar for both cements. Conclusion: Utilization of the Portland cement in Dentistry can be considered.